CLINICAL-NEUROLOGICAL, IMMUNOLOGICAL INDICATORS AND HLA ANTIGENS IN RHEUMATOID ARTHRITIS IN THE UZBEK POPULATION - Aslanova, S.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. In rheumatoid arthritis, pathological changes in the joints affect the segment of the apparatus of the spinal cord, its roots and peripheral nerves, as well as the segmental structures of the nervous system. Immunological, immunogenetic and neurophysiological changes due to the development of rheumatoid arthritis are not well understood, which complicates the development of criteria for early diagnosis. and methods of their complex therapy. Material. 142 patients with rheumatoid arthritis, aged 16-70 years of the Uzbek population and other nationalities. Conclusion. According to rheumatoid arthritis, diffuse damage to the nervous system with dysfunction of the autonomic departments, an early disorder of cerebral and peripheral hemodynamics, the bioelectrical activity of the cerebral cortex, and a violation of higher cortical functions were observed. Timely complex therapy had a positive effect on the somatic, neurological and immune statuses of the body and contributed to the regression of neurological symptoms.